The Effect of Modeling on Self-Efficacy and Flow State of Adolescent Athletes Through Role Models - Lee, Seungjoo; Kwon, Sungho; Ahn, Jihoon (Frontiers in Psychology, 2021)
This study aimed to verify the effects of role modeling on adolescent athletes’ self-efficacy and flow state. The subjects were middle school and high school athletes registered with the Korean Sport & Olympic Committee. From the collected data, descriptive statistics, confirmatory factor analysis, correlation analysis, and structural equation model analysis were performed. To verify the mediating effects of self-efficacy in the relationship between modeling and flow state, structural equation modeling analysis was conducted. The direct effects of adolescent athlete modeling on flow state (β=.416, B=.244, p<.01) and self-efficacy (β=.479, B=.500, p<.01) were all significant, and the direct effects of self-efficacy on flow state (β=.404, B=.227, p<.01) were also significant. Furthermore, it was confirmed that the indirect effect of modeling on flow state (β=.194, B=.114, p<.01) was significant, and that the partial mediated effects of self-efficacy were significant. Thus, we confirmed that when adolescent athlete use modeling through a role model, their self-efficacy increased which in turn led to a positive effect on the ability to achieve a flow state.